Production and Characterization of Adsorbent from Oyster Shell (Crassostrea gigas) Using Physics and Chemical Activation with ZnCl2 and Its Application for Removal of Hexavalent Chromium - Lia Handayani; Azwar Thaib; Nurhayati Nurhayati; Yayuk Astuti; Adi Darmawan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Abstract: Oyster shell waste has been investigated as a raw material for making adsorbents that will be activated. Physical activation uses temperatures of 500 ºC, 600 ºC, 700 ºC, 800 ºC, 900 ºC and chemical activation uses ZnCl2 with a concentration of 1 %, 5 %, 10 % and 15 %. Based on the analysis of the characteristics that have been carried out for physically activated adsorbents, the oyster shell calcined at 800 ºC produces the best characteristics, it is a radius of 35.11 Å with a percentage of removal of 38.04 %, as well as the results of the FTIR, XRF and SEM analysis gives the best results among others. Whereas for chemically activated adsorbents, the use of activator ZnCl2 10% produces adsorbents with the best characteristics among others with a radius of 84.14 Å and removal percentage of 65.68 %, the best results for adsorbents activated using 10% ZnCl2 are also supported by analysis results given by FTIR, XRF, and SEM.Keywords: Adsorbent; BET; Cr6+; Oyster Shell Waste; XRF Abstrak: Cangkang tiram (Crassostrea gigas) telah diteliti sebagai bahan baku pembuatan adsorben yang akan diaktivasi secara fisika dan kimia. Pembuatan adsorben dengan aktivasi secara fisika menggunakan variasi suhu 500 ºC, 600 ºC, 700 ºC, 800 ºC dan 900 ºC. sedangkan aktivasi kimia yaitu menggunakan aktivator ZnCl2 menggunakan variasi konsentrasi 1 %, 5 %, 10% dan 15 %. Berdasarkan analisa karakteristik yang telah dilakukan untuk adsorben-adsorben yang telah diaktivasi secara fisika, cangkang tiram yang di kalsinasi pada suhu 800ºC menghasilkan karakteristik yang paling baik, yaitu radius pori-pori 35,11 Å dengan persentase penyisihan sebesar 38,04 %, begitu pula dengan hasil analisa FTIR, XRF dan SEM memberikan hasil terbaik diantara yang lain. sedangkan untuk adsorben-adsorben yang diaktivasi secara kimia, penggunaan aktivator ZnCl2 10% menghasilkan adsorben dengan karakteristik yang paling baik diantara lainnya dengan radius pori-pori 84,14 Å dan persentase penyisihan sebesar 65,68%, hasil terbaik untuk adsorben yang diaktivasi menggunakan ZnCl2 10 % juga didukung oleh hasil analisa dari FTIR, XRF dan SEM.